Q-Rhetoric and Controlled Equivocation: Revising "The Scientific Study of Subjectivity" for Cross-Disciplinary Collaboration. Issue 2 (3rd April 2019) - Druschke, Caroline Gottschalk; Booth, Eric G.; Lundberg, Emma
ABSTRACT: This article offers a revision to an existing social science methodology, Q methodology, through "Q-Rhetoric." After detailing Q methodology's theoretical underpinnings and practical method, and persistent critiques of the methodology, the article employs perspectives from rhetorical theory and Amerindian anthropology to suggest a methodological correction. It concludes by detailing the use of Q-Rhetoric to intervene in a Wisconsin stream management controversy, proposing Q-Rhetoric as a pragmatic and theoretically sound methodology for working across disciplinary divides.